Analisis Swot Pada Usaha Mikro, Kecil Dan Menengah (UMKM) (studi kasus pada salad buah GEN Z) - Helvi Viola Sari; Daspar Daspar (CV. ITTC INDONESIA, 2025)
This study aims to analyze the development strategy of Gen Z Fruit Salad business in Bekasi through the SWOT approach. This MSME is present as a solution to the low consumption of fruit by the Indonesian people by offering healthy, practical products that are in line with current lifestyle trends. The research method used is quantitative descriptive with non-participant observation techniques. The results of the analysis show that Gen Z Fruit Salad has strengths in the form of product innovation, use of local raw materials, and attractive branding. However, internal weaknesses such as limited production and distribution are still the main obstacles. Opportunities from increasing awareness of healthy lifestyles and government support for MSMEs provide good prospects, even though they must face threats such as fluctuations in fruit prices and tight market competition. Based on the SWOT quadrant diagram, this business is in Quadrant III, which indicates the need for a survival strategy. Strategic recommendations include increasing production capacity, expanding distribution, utilizing digital media, and product innovation to reach a wider market. The results of this study are expected to be a reference in the development of similar MSMEs in the healthy culinary sector.